2007
DOI: 10.1177/154405910708600806
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil Hyper-responsiveness in Periodontitis

Abstract: Peripheral neutrophil hyper-responsiveness in chronic periodontitis leads to excessive reactive oxygen species (ROS) production. We aimed to determine whether neutrophil hyper-responsiveness was constitutive or reactive, and to discover the effect of non-surgical therapy. Peripheral blood neutrophils from patients (n = 19), before and 3 months after therapy, and matched control individuals were Fc gamma-receptor-stimulated with/without priming with P. gingivalis and F. nucleatum. Total and extracellular ROS we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
183
1
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(195 citation statements)
references
References 26 publications
8
183
1
3
Order By: Relevance
“…Higher concentrations of this protein in GCF may facilitate recruitment of PMNs at sites of inflammation. This may be relevant in view of the potential constitutive PMN hyper-reactivity in periodontitis patients (Matthews et al, 2007).…”
Section: Identification and Quantification Of Gcf Proteinsmentioning
confidence: 99%
“…Higher concentrations of this protein in GCF may facilitate recruitment of PMNs at sites of inflammation. This may be relevant in view of the potential constitutive PMN hyper-reactivity in periodontitis patients (Matthews et al, 2007).…”
Section: Identification and Quantification Of Gcf Proteinsmentioning
confidence: 99%
“…The resultant collateral host tissue damage to the supporting periodontal tissues leads to progressive periodontitis and ultimately culminates in tooth loss (6). Several studies have demonstrated that PBN from chronic periodontitis patients are not only hyperreactive, in response to Fc␥R stimulation by periodontal pathogens, but also hyperactive, with respect to baseline unstimulated ROS production (7)(8)(9)(10). Although a host molecular defect in intracellular lipid signaling may explain peripheral neutrophil ROS hyperreactivity in the relatively rare form of the disease, localized aggressive periodontitis (11), this mechanism does not explain the patient predisposition observed in chronic periodontitis.…”
Section: P Eripheral Blood Neutrophils (Pbn)mentioning
confidence: 99%
“…Although a host molecular defect in intracellular lipid signaling may explain peripheral neutrophil ROS hyperreactivity in the relatively rare form of the disease, localized aggressive periodontitis (11), this mechanism does not explain the patient predisposition observed in chronic periodontitis. The underlying mechanism(s) responsible for the hyperinflammatory neutrophil phenotype seen in chronic periodontitis (the commonest form of the disease) is currently unknown, although analyses indicate that it is not a result of altered adhesion molecule (7) or Phox gene (10) expression, polymorphisms in Fc␥R (8,12), or in vitro priming by cytokines or LPS (13,14). Furthermore, the association of periodontitis with increased relative risk for cardiovascular disease, fatal coronary events (15), and ischemic stroke (16), and the demonstrable medium-term reductions in vascular endothelial dysfunction following aggressive periodontal therapies (17), emphasize the potential impact of inflammatory periodontitis on peripheral macrovascular disease.…”
Section: P Eripheral Blood Neutrophils (Pbn)mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to their role as a first line of defense against pathogens, neutrophils can also mediate tissue destruction in inflammatory diseases (Hansen, 1995). Periodontal disease, including gingivitis, has been associated with an increase in the number and activation state of circulating neutrophils (Loos et al, 2000;Kowolik et al, 2001;Matthews et al, 2007). Activated neutrophils release highly cytotoxic oxidants, which can be assessed by luminol-enhanced chemiluminescence, as well as proteolytic enzymes, both of which have the potential for tissue damage.…”
mentioning
confidence: 99%